Potential of Phytochemicals in management of cognitive disorders- An Update - joshi, Hanumanthachar; Jagadeesh, Patil; Parle, Milind (Pharmacognosy Reviews)
Memory function is vulnerable to a variety of pathologic processes including neurodegenerative diseases, strokes, tumors, head trauma, hypoxia, cardiac surgery, malnutrition, attention-deficit disorder, depression, anxiety, the side effects of medication, and normal ageing. Normal ageing is known to deteriorate memory in human beings. Oxygen free radicals, the harmful byproducts of oxidative metabolism are known to cause organic damage to the living system, which may be responsible for the development of Alzheimer’s disease (AD) in elderly. AD is a progressive neurodegenerative brain disorder that occurs gradually and results in memory loss, unusual behavior, personality changes and ultimately death. It is the most common form of onset of adult dementia and attention deficit disorders. Nootropics represent a new class of psychotropic agents with selective facilitatory effect on integrative functions of the central nervous system, particularly on intellectual performance, learning capability and memory. AD begins as a deficiency in the production of the neurotransmitter acetylcholine. The National Institute of Health predicts, if the current trend continues, there will be more than 8.5 million AD patients by the year 2030 in USA alone. Amnesic mild cognitive impairment represents a transitional state between the cognitive changes of normal ageing and the earliest critical features of Alzheimer’s disease. Although there is no cure for dementia of AD type at present, alternative pharmacologic treatment modalities can reduce the symptoms of cognitive impairment and slow disease progression. Presently, the allopathic system of medicine principally relies on nootropic agents, such as piracetam, aniracetam, fosracetam, nefiracetam, etc., and anticholinesterases, such as Donepezil® and tacrine which are commonly used for improving mood and behavior. However the Donepezil® have adverse side effect on cholinergic symptoms particularly gastrointestinal symptoms like nausea, vomiting and diarrhea. Tacrine has adverse effect on liver toxicity, as shown by elevated serum amino transferases. Since allopathic system of medicine is yet provide a radical cure of AD, it is worthwhile to look for new direction, which would minimize the memory loss of patients with neuropsychiatric disorder. The utility of traditional medicines may be explored for treating patient with dementia. In this review, the phytochemicals proved to be of potential in the modulation of cognitive dysfunctions particularly Alzheimer’s related disorders, have been discussed with special reference to their possible mechanism of action.